Governance for e-learning ecosystem - Chang, Vanessa; Uden, L. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Governance has emerged as an important issue for organisations across the world. Governance is the combined activities of developing and managing cohesive and consistent policies, processes and decisions right for a given area of responsibility. For an e-learning ecosystem to work effectively, it is essential that we have the right regulatory, technological and social conditions. This paper discusses a framework to support the successful implementation of an e-learning system includes (1) organisational decision making structures, (2) processes which include operational and technical supports, and (3) communications and relational mechanisms. Six characteristics and dimensions of Darking's [12] digital ecosystem governance were used to enhance the framework. E-learning information seurity governance is also discussed in the paper. The underlying goals for adopting e-learning governance practices are improvement of business performance and conformance to regulations. This paper discusses governance for e-learning ecosystems within the digital business ecosystms (DBE).